Augmented Reality in STEM Education: Trends and Insights from 2012 to 2021 - Prelia Dwi Amanah; Rahmatullah Rahmatullah; Gunawan Gunawan (Indonesian Publication Center, 2022)
This study aims to analyze trends and developments in research on augmented reality (AR) in Science, Technology, Engineering, and Mathematics (STEM) education during the 2012–2021 period through a descriptive bibliometric analysis approach. Data were obtained from the Dimensions.ai and Publish or Perish (PoP) database using the keyword combination